(untitled) (Avocetta, 2017)
A significant part (about 20%) of the population of the Golden Eagle Aquila chrysaetos in the Central Apennines breeds in the mountains of Lazio. The breeding performance of these pairs has been monitored since the midseventies of the last century (Novelletto & Petretti 1980, Allavena et al. 1987, Borlenghi 1992, Zocchi 1992, Zocchi & Panella 1996, Borlenghi & Corsetti 1996, 2002, 2004, Borlenghi 2005, Borlenghi et al. 2014). Since 2014 this activity was included in the “Monitoring Net of Rupicolous Raptors” of the Lazio region, in accordance with the Birds Directive (2009/147/EC). In recent years we have seen the participation by staff members from the protected areas in the monitoring of these birds. The main purpose of the Golden Eagle breeding monitoring project in Lazio is to obtain all the necessary information to improve the conservation of this species through specific actions. The area used by this species in Lazio, is estimated at 3,800 km² (Borlenghi et al. 2014), and corresponds to the main mountainous systems of the region. Breeding pairs are distributed in the Laga Mts, Reatini Mts, Carseolani Mts, Lucretili Mts, Simbruini Mts, Ernici Mts, Mt. Cornacchia Group, Meta Mts, Mt. Cairo group and Lepini Mts. In four other mountainous systems (Mt. Pozzoni, Mt. Giano, Duchessa and Aurunci Mts) it’s possible to observe immature pairs, not yet nesting, and/or floaters (Fig. 1). In all these territories the annual monitoring has been carried on in the January-August period.